Hop Kilning Temperature Sensitivity of Dextrin-Reducing Enzymes in Hops. (10th January 2022) - Rubottom, Lindsey N.; Lafontaine, Scott R.; Hauser, Dean G.; Pereira, Cliff; Shellhammer, Thomas H.
Abstract: Kilning represents a considerable energy input in the production of hops and has a direct impact on hop quality. This study investigates how kilning temperature impacts the dextrin-reducing enzymes in hops in two major aroma cultivars, Amarillo ® and Simcoe ®, by manipulating kiln temperature on a pilot and commercial-scale. There is evidence that during dry-hopping, dextrin-reducing enzymes present in or on hops hydrolyze nonfermentable dextrins into fermentable sugars. A wide range of kilning temperatures (120–180 °F/49–82 °C) were used to examine how dextrin-reducing enzymes respond to thermal treatment during hop drying. Amarillo ® hops were dried using pilot- and commercial-scale kilns in Washington, Idaho, and Oregon over two harvest years (2018 and 2019). Simcoe ® hops were dried in half-sized commercial-scale kilns at two locations in Washington over two harvest years (2018 and 2019). A significant temperature dependency on the dextrin-reducing enzymatic power of the hops was observed. Higher kiln temperatures resulted in significant reductions in enzyme activity, which in turn reduced fermenter hop creep or dry-hop induced overattenuation. These results suggest increases in kilning temperature reduce the enzymatic activity of hops.